Evaluation of biochemical parameters inRubus tereticaulistreated rats and its implications in wound healing - ŞEN, ALİ; ŞENER, AZİZE; AKSOY, HALİL; BİNGÖL ÖZAKPINAR, ÖZLEM; TETİK, ŞERMİN; ŞEKERLER, TURGUT (SPRINGER, 2020)
We evaluated the effects ofRubus tereticaulisin healing process by determining the total carbonyl content, collagen synthesis, and total protein level on rat wounded tissues. Wounds were performed in the back of 54 Wistar rats, using a biopsy punch instrument with 0.6 mm in diameter. Rats were randomly divided into three groups: (i) un-treatment wounds group served as controls, (ii) Madecassol (R) used as positive control group, and (iii) the application of topical cream ofR. tereticaulisserved as treatment group of wound healing. The animals were killed at the end of experiment under anesthesia with ketamine, and tissue samples were collected for the evaluation at three times intervals (3rd, 7th, and 14th day). The wounded areas were analyzed for total carbonyl content, collagen, and total protein levels by HPLC, ELISA, and spectrophotometric methods, respectively. Total carbonyl content in the treatment group was significantly lower in comparison with control group on 3rd day (2.839 +/- 0.438 vs. 3.216 +/- 0.216 nmol carbonyl/mol protein;p < 0.5) and 14th days (4.222 +/- 0.128 vs. 4.784 +/- 0.077 nmol carbonyl/mol protein;p < 0.05), respectively. New collagen formation on the wound sites after the initial injury was noted in the treated and positive control groups (5.310 +/- 0.331 vs. 5.164 +/- 0.377 mg collagen/g wet tissue) at the 3rd day than control group (2.180 +/- 0.718 mg collagen/g wet tissue,p < 0.01), and in treated and positive control groups at 7th day (9.654 +/- 0.201, 9.053 +/- 1.062 mg collagen/g wet tissue,p < 0.01); and in treated and positive control groups at 14th day (8.469 +/- 0.236, 5.631 +/- 0.531 mg collagen/g wet tissue, respectively;p < 0.05) in comparison with the control group. Total protein level of samples did not change significantly between the groups. Thus, application ofR. tereticaulisameliorated the wound healing process in rats as it facilitated collagen formation through healing of the wound. Evaluating total carbonyl content by HPLC could be useful as an advance procedure for quantification of healing.
Keywords: Wound healing; Rubus tereticaulis; carbonyl content; HPLC; Biochemical assessments; Rat; PROTEINS; PLASMA; DAMAGE